2016
DOI: 10.1186/s12889-016-3274-8
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of HIV testing and counseling, risk perception and linkage to HIV care among Thai university students

Abstract: BackgroundHIV testing and counseling (HTC) with linkage to care after known infection are key components for HIV transmission prevention. This study was conducted to assess HTC uptake, HIV risk perception and linkage to care among Thai university students.MethodsAn outreach HTC program was conducted in a large public university in Thailand from January 2013 to December 2014. The program consisted of brief HIV knowledge assessment, free HTC, HIV risk assessment and education provided by the healthcare personnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
3
16
1
Order By: Relevance
“…Our study revealed a high, but yet below the target, proportion of HIV-infected MSM who were diagnosed, but MSM have, in general, higher risk perception and willingness to access HIV testing services than other population groups [ 15 , 16 ]. Interestingly, a high percentage of PWID with HIV were diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed a high, but yet below the target, proportion of HIV-infected MSM who were diagnosed, but MSM have, in general, higher risk perception and willingness to access HIV testing services than other population groups [ 15 , 16 ]. Interestingly, a high percentage of PWID with HIV were diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Nunn et al, 2011) and incarcerated men (Golin, Barkley, Biddell, Wohl, & Rosen, 2017). Correlation between perceived and actual HIV risk varies, with some studies indicating moderate perception accuracy (Khawcharoenporn, Chunloy, & Apisarnthanarak, 2016; Mgbere et al, 2013) and others showing more extreme rates of risk underestimation (Clifton et al, 2016; Fan et al, 2014; Mumtaz et al, 2014). Discrepancies between perceived and actual risk are a significant public health challenge because it indicates that those who are most vulnerable to HIV (and thus PrEP eligible) may not recognize their risk or seek out services and are in need of targeted outreach.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of HIV status and uptake of HIV Testing Services (HTS) varies considerably across different settings [ 11 13 ]. In a study in Malawi, HTS uptake ranged from 16.9% among the poor to 25.4% among individuals in the higher wealth quartile [ 14 ] while elsewhere uptake ranged from 27% to over 76.5% [ 15 18 ]. In Uganda, overall uptake of HTS among adolescents is less than 20%, however the reasons behind this low uptake are not well documented.…”
Section: Introductionmentioning
confidence: 99%